THE CONSTITUTION AND THE LEGAL FOUNDATIONS OF COMBATING CORRUPTION - Zokirova O. G., (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The article provides a scientific substantiation of the new stage in combating corruption in connection with the newly revised Constitution.